Pengembangan Media Pembelajaran Interaktif Matme Berbantuan Aplikasi Articulate Storyline Untuk Meningkatkan Penalaran Siswa Pada Materi Bilangan Bulat Kelas VII SMP Negeri Tonala Kabupaten Bolaang Mongondow Selatan Sulawesi Utara - Israwin Saman; Tedy Machmud; Franky Alfirst Oroh (JEMS: Jurnal Edukasi Matematika dan Sains, 2026)
Articulate Storyline is an ICT software that functions to create interactive audio-visual-based learning media. This application allows users to customize templates and characters as needed, making it easier for teachers to deliver material in an interesting and easy-to-understand way for students. Articulate Storyline is a useful tool for digital learning designers of all levels, from beginners to experts. In this study, the Articulate Storyline application was used to develop interactive learning media called "MatMe" on integer material for class VII SMP Negeri Tonala. This media is designed to improve students' understanding through audio-visual features that allow them to learn anytime and anywhere. This study aims to describe the process of developing the Articulate Storyline application and evaluate the "MatMe" learning media based on the criteria of validity, practicality, and effectiveness. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The results of the study showed that the interactive learning media "MatMe" was able to improve students' reasoning skills in integer material. This media is considered valid, practical, and effective to be applied in mathematics learning, so it is worthy of being used as an alternative learning media in class VII of Tonala State Middle School. Keywords: interactive media, ; Android ; articulate storyline; Integers